2015
DOI: 10.1007/s00238-015-1110-5
|View full text |Cite
|
Sign up to set email alerts
|

Medial sural artery perforator flap: a challenging free flap

Abstract: BackgroundOral and extremity defect reconstruction can often require a flap that is thin, and traditionally, the radial forearm free flap has been used, however, this has significant donor site morbidity. Over the last decade, the medial sural artery perforator (MSAP) flap has emerged as a possible alternative with lower donor site morbidity. We present our experiences and review the literature regarding this promising but challenging flap.MethodsThe study was a retrospective case series in a university hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 24 publications
5
24
2
3
Order By: Relevance
“…Kao et al directly compared the MSAP and RFFF, demonstrating a 100% success rate in both flaps but with better subjective functional and cosmetic outcomes in the MSAP cohort. Although the RFFF risks tendon exposure, always requires coverage with a skin graft or other method, and is in a visible area of the forearm, we have shown the MSAP donor site can be well‐hidden in the medial leg (Fig. ).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Kao et al directly compared the MSAP and RFFF, demonstrating a 100% success rate in both flaps but with better subjective functional and cosmetic outcomes in the MSAP cohort. Although the RFFF risks tendon exposure, always requires coverage with a skin graft or other method, and is in a visible area of the forearm, we have shown the MSAP donor site can be well‐hidden in the medial leg (Fig. ).…”
Section: Discussionmentioning
confidence: 87%
“…The same surgical method was used in each case, similar to the surgical technique already reported in previous studies . A two‐team approach was used in each case.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we preferred ulnar forearm flap due to its superior donor site cosmesis (Hsiao et al, 2016). Additionally, we found that MSAP flap can be another suitable choice, with its similar characteristics to the forearm flap, but less donor site morbidity (Ives & Mathur, 2015;Kao, Chang, Wei, & Cheng, 2009;Nugent, Endersby, Kennedy, & Burns, 2015;Toyserkani & Sørensen, 2015;Xie & Chai, 2012). With careful planning and meticulous dissection, we tend to gradually avoid the forearm flap and use this flap as a free flap in nose resurfacing.…”
Section: Discussionmentioning
confidence: 99%